Aeromonas veronii an emerging pathogen: A brief review - Henry Junior Parra-Vera; Galo Guillermo Farfán-Cano; Dayci Colombia Buele-Chica (School of Medicine, Universitas Syiah Kuala, 2023)
Aeromonas veronii, a Gram-negative bacterium, thrives in aquatic environments and is linked to diseases in animals and humans. The primary aim of this review was to provide an extensive description of A. veronii as an infectious agent, focusing on its microbiological attributes, pathogenesis, distribution, virulence, and antimicrobial resistance. An exhaustive review of the available medical literature was conducted. Theoretical sources were scrutinized to determine the taxonomic and microbiological properties of A. veronii. The pathogenic characteristics of the bacterium were examined, with a special emphasis on virulence factors, epidemiology, zoonotic potential, and antimicrobial resistance. Additionally, pertinent data regarding the geographic distribution of A. veronii from various origins, encompassing the environment, farm animals, and clinical cases in humans, were synthesized. This investigation illuminated the significant microbiological traits of A. veronii, including its adaptability to various environmental conditions and its ability to persist in crucial sources of infection, such as poultry feces and processing water. In addition, specific A. veronii strains, along with other Aeromonas species, have been identified as emerging pathogens in foodborne disease outbreaks in developing nations, accentuating the importance of rigorous hygiene measures in food production and handling. The study underscored the opportunistic nature of A. veronii in immunocompromised individuals, emphasizing the necessity for active surveillance and stringent hygiene practices to mitigate exposure and transmission among vulnerable populations. Furthermore, the relevance of the virulence factors of A. veronii, including biofilm formation and the presence of antimicrobial resistance genes, was emphasized, underscoring the importance of ongoing research to understand and combat antimicrobial resistance in this bacterium.